Review of Gabriele Münnix: Das Bild vom Bild: Bildsemiotik und Bildphänomenologie in interkultureller Perspektive - Riccardo Pozzo (Proceedings (European Academy of Sciences and Arts))
Images shape how we perceive reality, how we think and feel, and how we live together. Gabriele Münnix shows that cultural traditions play an essential role in these processes. Her book is about providing an overview of the different ways of dealing with images. She presents authoritative approaches to the philosophy of images such as those of C.S. Peirce, Edmund Husserl, Martin Heidegger, Jean-Paul Sartre, Nelson Goodman, Maurice Merleau-Ponty, Michel Foucault, Jacques Derrida, Umberto Eco, and of others. What is new in her analysis is the inclusion of the intercultural perspective, which makes a new approach to the controversies about the nature of the image as signs or as presence possible that can also be effective in establishing a relation between philosophy of religion an undogmatic metaphysics.